Mortality risk associated with combinations of loneliness and social isolation. Findings from The Irish Longitudinal Study on Ageing (TILDA) - Ward, Mark; May, Peter; Kenny, Rose (My University, 2021)
Background: Social distancing and similar measures in response to the coronavirus disease 2019 pandemic have greatly increased loneliness and social isolation among older adults. Understanding the association between loneliness and mortality is therefore critically important. We examined whether combinations of loneliness and social isolation, using a metric named social asymmetry, was associated with increased mortality risk. Methods: The sample was derived from participants in The Irish Longitudinal Study on Ageing, a nationally representative sample of community-dwelling older adults aged ≥50. Survey data were linked to official death registration records. Cox proportional hazards regressions and competing risk survival analyses were used to examine the association between social asymmetry and all-cause and cause-specific mortality. Results: Of four social asymmetry groups, concordant low lonely (low loneliness, low isolation) included 35.5% of participants; 26.4% were concordant high lonely (high loneliness, high isolation); 19.2% were discordant robust (low loneliness, high isolation) and 18.9% discordant susceptible (high loneliness, low isolation). The concordant high lonely (hazard ratio [HR] = 1.43, 95% confidence interval [CI]: 1.09–1.87) and discordant robust (HR = 1.37, 95% CI: 1.04– 1.81) groups had an increased mortality risk compared to those in the concordant low lonely group. The concordant high lonely group had an increased risk of mortality due to diseases of the circulatory system (sub-distribution hazard ratio = 1.52, 95% CI: 1.03–2.25). Conclusion: We found that social asymmetry predicted mortality over a 7-year follow-up period. Our results confirm that a mismatch between subjective loneliness and objective social isolation, as well as the combination of loneliness and social isolation, were associated with an increased all-cause mortality risk.
PUBLISHED
Keywords: mortality, loneliness, social isolation, social asymmetry, ageing, older people; Ageing